Pull-up Counter Device Using Arduino Uno for Fitness Purposes - Sulaiman, Suliana; Ahmad Shukri, Ahmad Ayyadi; Abd Wahid, Rohaizah; Mansor, Marzita; Ariffin, Asma Hanee (International Journal of Recent Technology and Applied Science (IJORTAS), 2022)
A pull-up is a type of upper-body exercise that involves the use of both hands. It works by raising the body's head and shoulders and bending the elbows, and extending the shoulders. It can be performed anywhere and is a great way to tone and expand various muscle groups. This study aims to design a device that can count and track the number of pull-up exercises. Pull-Up Counter Device was developed using the Rapid Prototyping model. The product was evaluated by 30 respondents. The result shows that 83.33% of the users strongly agree that the device can display the correct pull-up record on the LCD, and 50% strongly agree that the device can detect pull-up position correctly.